Digital Health Technology on Patient Recovery and Nurse Performance in Indonesia - Dwiyana, Bara Mira; Nurulhuda, Uun (West Science Interdisciplinary Studies, 2024)
This study investigates the impact of digital health technology, nurse competence, patient safety protocols, and organizational support on patient recovery and nurse performance within the Indonesian healthcare sector. Utilizing a quantitative approach, data were collected from 120 healthcare professionals through structured questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that digital health technology, nurse competence, and patient safety protocols positively influence patient recovery, while organizational support and digital health technology significantly enhance nurse performance. Organizational support and patient safety protocols emerged as the strongest predictors of nurse performance and patient recovery, respectively. These results suggest that a comprehensive approach integrating technological, safety, and support factors can substantially improve healthcare outcomes. This study offers practical recommendations for healthcare administrators and policymakers to enhance healthcare quality through strategic investments in digital tools, training, safety protocols, and supportive work environments.